A Survey of Experiences with Emerging Market Sovereign Debt Restructurings. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper takes stock of past episodes of debt restructuring and reviews the relevant literature. Based on cross-country experience from the late 1990s through 2010 of emerging markets it offers some stylized facts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet